Effects of outcome uncertainty related to gain and loss, performance feedback, and individual differences during a cognitive control task - Biagi, Nicolo; Byrne, Phoenix; Morriss, Jayne (Frontiers in Psychology, 2025)
IntroductionOutcome uncertainty is known to engage motivational and emotional phenomena. However, there remain questions as to how outcome uncertainty related to gain and loss and information availability via performance feedback interact to impact motivational and emotional phenomena: (1) generally, and (2) in relation to individual differences in intolerance of uncertainty, and current symptoms related to anxiety and depression.MethodsTo address these gaps in the literature, we manipulated the level of outcome uncertainty (gain, loss, none) and performance feedback (present, absent) during an online cognitive control task (n = 69), to examine how these factors impact different read-outs: subjective emotional responses (valence, arousal), task accuracy, reaction times, and fixation count. Self-reported intolerance of uncertainty and symptoms of general distress, anxious arousal, and anhedonic depression were also collected.ResultsOutcome uncertainty related to loss and gain, compared to no outcome, was associated with higher arousal and higher task accuracy. Uncertainty about task performance through the absence of performance feedback lowered arousal, dampened positive affect, and led to demotivation (i.e. lowered task accuracy and fixation count). Individual differences in intolerance of uncertainty and symptoms of anxiety and depression were specifically associated with different self-reported experiences of emotion (i.e. valence) and motivational engagement (i.e. fixation count).DiscussionThese findings suggest that outcome uncertainty and performance feedback, as well as intolerance of uncertainty, and anxious/depressive traits differently impact motivation and emotion.